Temporal changes in attenuation associated with the 2004 M6.0 Parkfield earthquake. Issue 2 (26th February 2013) - Kelly, C. M.; Rietbrock, A.; Faulkner, D. R.; Nadeau, R. M.
Abstract : [1] Elevated seismic attenuation is often observed in fault zones due to the high degree of fracturing and fluid content. However, temporal changes in attenuation at the time of an earthquake are poorly constrained but can give indications of fracture damage and healing. In this study, spectral ratios between earthquakes within repeating clusters are calculated in an attempt to resolve temporal variations in attenuation at the time of the 2004 M6.0 Parkfield earthquake. A sharp increase in attenuation is observed immediately after the earthquake, which then decays over the next 2 years. Influences of intercluster magnitude variations, time window length and previously reported postseismic velocity changes are investigated. The postseismic decay is fit by a logarithmic function. The timescale of the decay is found to be similar to that in GPS data and ambient seismic noise velocities following the 2004 M6.0 Parkfield earthquake. The amplitude of the attenuation change corresponds to a decrease of approximately 10% in Q p at the time of the earthquake. The greatest changes are recorded on the northeast of the fault trace, consistent with preferential damage in the extensional quadrant behind a north‐westerly propagating rupture tip. Our analysis suggests that significant changes in seismic attenuation and hence fracture dilatancy during coseismic rupture are limited to depths of less than about 5 km. Key Points: P‐wave attenuation is found to evolve at the time of a M6.0 earthquake Lateral and depth variation of attenuation changes at Parkfield are investigated